Customers as Good Soldiers: Examining Citizenship Behaviors in Internet Service Deliveries - Groth, Markus (Journal of Management, 2005)
Organizational citizenship behavior (OCB) research is extended to the customer domain by examining the role of customer behavior in Internet service deliveries. Based on the OCB framework, it was hypothesized that a conceptual distinction between in-role behaviors (i.e., task performance) and extra-role behaviors (i.e., citizenship behavior) can be extended to customers who participate in service delivery. Survey data show that customers differentiate coproduction behaviors from customer citizenship behaviors. Furthermore, these two behaviors had different sets of predictors. Theoretical and practical implications are discussed from the perspective of OCB theories.